Investigation of optimal inflation targets for 15 major oil exporting Sub-Saharan African countries: A panel threshold estimation. Issue 49 (15th April 2020) - Abdulqadir, Idris Abdullahi; Chua, Soo Y.; Mohd, Saidatulakmal
Abstract : Purpose: The purpose of this paper is to investigate the optimal inflation targets for an appropriate exchange rate policy in 15 major oil exporting countries in Sub-Saharan African (SSA). Design/methodology/approach: Dynamic heterogeneous panel threshold techniques are used via threshold-effect test and threshold regression. This procedure is achieved through a grid search and bootstrapping replications method to stimulate the asymptotic distribution of the likelihood ratio test of the null hypothesis on no-threshold as against the alternative hypothesis. The p -values validate the threshold estimates. Findings: Findings revealed that the optimal inflation target has a turning point and its impact on the real exchange rate is up to a threshold level of 14.47 per cent. Furthermore, the inflation rate above the threshold level overwhelmingly revealed its effect on real exchange regimes. Research limitations/implications: It would have been a good idea to investigate optimal inflation targets for all African countries but due to inadequate data the selection criteria was narrowed to oil-exporting countries in Sub-Saharan Africa. Practical implications: Inflation targeting beyond the threshold level would have serious implications on the monetary policy. Originality/value: To the best of the knowledge, this is the first study to look at optimal inflation targets for 15 major oil exporting countries in general and SSA countries in particular. The findings provide a critical analysis of an inflation regime for a typical oil-producing country that oil exports being their source of revenue.